PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATERI RUANG DIMENSI TIGA DENGAN PENDEKATAN KONTEKSTUAL PESERTA DIDIK KELAS XII SEMESTER GANJIL SMAN 1 POLEWALI - mulhayu, Andi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
The success of this study was indicated by an increase in students' learning motivation above 75%, an increase in learning outcomes above the KKM, and a minimum percentage of classical learning mastery of 75%.This research is classroom action research. The learning used in this research is contextual. The subjects of this study were class XII students at SMA Negeri 1 Polewali for the 2021/2022 academic year, namely 36 students. Data was collected through documentation, interviews, tests, observations, and questionnaires. The collected data were analyzed using descriptive analysis and calculating the average value and percentage.Based on the research results, the percentage of learning motivation from cycle I to cycle II increased from 63.04% to 76.33% or 13.29%. There was an average increase in student learning outcomes from 72.01 to 75.32 or 3.31 points. The students' classical learning completeness increased from 68.75% to 79.41% or 10.66%.